Iron and zinc variation along the grain length of different Thai rice varieties - Suwannee Laenoi (2018)
This study examined the distribution of iron (Fe) and zinc (Zn) along the grain length of seven rice varieties. The experiment was conducted in a completely randomized design with two factors (variety and grain fraction) and three independent replications. Samples of brown and white rice of six common Thai rice varieties and a high Fe and Zn variety, IR68144, were transversely cut into three fractions per grain (basal, middle, and distal) with approximately the same length in each fraction. The concentration of Fe and Zn was determined by the dry ashing method and quantified using atomic absorption spectrometry. The middle grain fraction of brown rice was found to have the lowest Fe and Zn with greater concentration of Fe and Zn in the basal (embryo end) than the other fractions. The rice varieties differed in the amount of Fe and Zn allocated to different fractions of the endosperm (white rice). The potential for loss of Fe and Zn during milling due to their uneven distribution along the grain length will become more significant when higher nutrient concentrations are involved, such as those achieved by biofortification efforts. Micronutrient distribution needs to be taken into consideration to ensure that rice consumers benefit from Fe and Zn biofortification.